Penentuan Rute Terpendek Pendistribusian Tabung Gas Lpg 3 Kg Pt. Fega Gas Palu Pratama Menggunakan Algoritma Tabu Search - Riswan; Sahari, A; Lusiyanti, D (Program Studi Matematika, Universitas Tadulako, 2019)
ABSTRACTDistribution is one of the important tools in the company business activities. The problem that is often occurred indistribution is the determination of the shortest route. The purpose of this study is optimitation distribution route of3 kg LPG gas cylinders which is carried out by PT. Fega Gas Palu Pratama in Palu City, considering that thiscompany has not used a particular method in determining the distribution route of 3 kg LPG gas cylinders. Themethod used in this study is the Tabu Search algorithm. The algorithm of the Tabu Search method are of follows,first by determine the initial solution using the closest Nearest Neighbor, determine alternatives by exchange 2points in the solution, evaluate alternative solutions, determine a new optimum solution, update the Tabu List, thenwhen the termination criteria are obtained then the Tabu Search algorithm will stop otherwise it will revert toexchanging 2 points evaluation. The process of calculating the Tabu Search algorithm is conducted manually andbuilt using MATLAB. Based on the research that has been done, it is obtained that the shortest, more efficient routeis 21.91 km which has reduction of 7.26 km from the initial route 29.17 km.Keywords : Algorithm Tabu Search, Distribution, Shortest Route.